Density functional theory studies on vibrational spectra (E)-N-(4-carboxylphenyl)-2-(1-(pyrazin-2- yl)ethylidene) hydrazinecarbothioamide - Abdullah, Erna Normaya; Abdul Aziz, Yang Farina (Institut Kimia Malaysia, 2013)
The reaction of 2-acetylpyrazine with methyl hydrazinecarbodithioate (2) formed methyl-2-(1-(pyrazin-2-yl)ethylidene)hydrazinecarbodithioate (3). The condensation reaction of (3) with 4-aminobenzoic acid produced the title compound (E)-N-(4-carboxylphenyl)-2-(1- (pyrazin-2-ethylidene) hydrazinecarbothioamide (1). The ligand has been characterized using elemental analysis and FT-IR as well as melting point determination. The vibrational wavenumbers and corresponding vibrational assignments were examined theoretically using the Gaussion09. Theoretical vibrational wavenumbers using DFT of B3LYP/6-311 G (d,p) basis set was compared with experimental FT-IR spectra and they were found to support each other.